CURRENT STATE AND ANALYSIS OF THE COMPETITIVENESS OF UKRAINIAN ENTERPRISES - NIEKRASOVA, Liubov; KRUPITSA, Iryna; SHEPELEVA, Olga; NAUMENKO Yuriі (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to an in-depth analysis of Ukrainian enterprises’ current competitiveness in the context of global economic transformations and internal challenges driven by financial instability, political factors, and the consequences of war. The study systematizes the key internal and external factors that directly affect enterprises’ ability to adapt to change and maintain or enhance their competitive positions. Particular attention is paid to competitiveness’s economic, technological, infrastructural, human resource, and regulatory determinants. Using a sectoral approach, the article examines the specifics of competitive advantage formation in Ukraine’s leading economic sectors — agriculture and industry. It is clarified that in the agricultural sector, the key drivers include precision farming, digital platforms, and automated accounting and monitoring systems. In contrast, in industry, they are modernizing production, implementing energy-efficient technologies, and using alternative energy sources. The article presents concrete examples of successful enterprises that have achieved high performance by integrating innovative approaches focused on sustainable production, resource conservation, and environmental safety. A separate focus of the research is the analysis of the role of state policy in creating a favorable environment for enhancing business competitiveness. The influence of tax incentives, subsidy programs, investment grants, and public-private partnership tools on activating business activity is examined. The necessity of regulatory reform, simplification of business conditions, and support for small and medium-sized enterprises as the foundation of economic resilience is substantiated. The article also outlines prospects for further growth in Ukrainian enterprises’ competitiveness through intensified investment in advanced technologies, scaling up digital transformation, modernizing production capacities, and entering new international markets. Conclusions are drawn regarding the need to develop an integrated competitiveness strategy that combines innovation-driven development, effective interaction with government institutions, and adaptation to contemporary global challenges.